Idiopathic chronic diarrhea associated with dysbiosis in a captive cynomolgus macaque (Macaca fascicularis). Issue 1 (23rd October 2019) - Koo, Bon‐Sang; Baek, Seung Ho; Kim, Green; Hwang, Eun‐ha; Oh, Hanseul; Son, Yeonghoon; Lim, Kyung Seob; Kang, Philyong; Lee, Hwal‐Yong; Jeong, Kang‐Jin; Kim, Young‐Hyun; Villinger, Francois; et al.
Abstract: Chronic inflammatory enteric diseases occur commonly in humans and animals, especially in captive bred macaques. However, information about the etiology of idiopathic chronic inflammatory diarrhea in cynomolgus monkeys is limited. In this paper, we reported the unusual case of idiopathic chronic diarrhea in a captive cynomolgus monkey based on microbial, imaging, and microbiome examinations.